كاریگەری ململانێی سیاسی لە پێكهێنانی سیماكانی كەسێتی كورددا - عبدللە, ئاسۆ ئیبراهیم; حسێن, شۆخان محمود (Sulaimani Journal for Humanities, 2021)
This research deals with the study of the political conflicts in Iraqi Kurdistan and their impact on the Traits of Kurdish personalities between the years 1991-2021. The researchers used the descriptive method in order to identify the impact of the political conflicts on the Traits of (cultural, social and psychological) characteristics in the Kurdish personality. The researchers concluded that the interior political conflicts in the Iraqi Kurdistan had a negative impact on social institutions, which led to the inability of these institutions to play their main role in the process of political socialization. On this basis, (social indifference, serving personal interests, inequality, lack of justice, social violence) appeared as social Traits in the Kurdish personalities. There have been changes in the cultural and political cultural and the value system throughout the various historical stages in Iraqi Kurdistan, which led to the emergence of many new cultural Traits in the Kurdish personality, including (indifference to cultural and political elements, as well as weakness of national affiliation). The results also showed that the political conflicts in Iraqi Kurdistan over the past thirty years, which are in the form of a circular ring revolving in the same path, negatively affected the psychological health of individuals and these effects were transmitted from one generation to the next, over generations and times. This led to the formation of many different psychological Traits in the Kurdish personality such as (anxiety, understanding/ sensitivity, intolerance, depression, pessimism, mistrust, aggression, self-love/selfishness. (